PREDICTION OF TÜRKİYE'S BURNED FOREST AREAS USING ARIMA MODEL - Bağcı, Kübra (Fırat University, 2023)
Abstract: Large-scale forest fires can cause significant ecological losses. Additionally, preserving forest areas may help to slow down climate change. Statistical models are one of the tools used in planning fire management strategies. In this study, the burned forest area of Türkiye is modeled using the Autoregressive Integrated Moving Average (ARIMA) method following the identification, estimation, validation, and forecasting steps. As is known the ARIMA analysis is one of the popular techniques used in time series analysis. Annual total burned forest areas in Türkiye over the period 1940-2021 are considered in the analysis. Three preliminary models are considered for evaluation of their modeling and prediction performances. The models' validities are investigated with Ljung–Box statistics, residual analysis, and cross-validation. According to the results, the ARIMA (3,1,0) model is found to be the most suitable model for predicting the future values of the burned forest area time series in Türkiye. Forecasts for Türkiye’s burned forest areas series are obtained for the next 3 years accordingly.

Büyük ölçekli orman yangınları önemli ekolojik kayıplara neden olmaktadır. Ayrıca ormanlık alanların korunması iklim değişikliğini yavaşlatmaya yardımcı olabilmektedir. İstatistiksel modeller, yangın yönetimi stratejilerinin planlanmasında kullanılan araçlardan biridir. Bu çalışmada, Türkiye'nin yanan orman alanı, tanımlama, tahmin, doğrulama ve öngörü adımları izlenerek Otoregresif Bütünleşik Hareketli Ortalama (ARIMA) yöntemi kullanılarak analiz edilmiştir. ARIMA yöntemi zaman serileri analizinde kullanılan popüler tekniklerden biridir. Analizde 1940-2021 yılları arasında Türkiye'deki yıllık toplam yanan orman alanı ölçümleri kullanılmıştır. Modelleme ve tahmin performanslarının değerlendirilmesi için üç model ele alınmıştır. Modellerin geçerliliği, Ljung–Box istatistikleri ve çapraz doğrulama ile araştırılmıştır. Sonuçlara göre, ARIMA (3,1,0) modeli Türkiye'nin yanmış orman alanı zaman serilerinin gelecek değerlerinin tahmin edilmesi için en uygun model olarak bulunmuş ve öngörüler önümüzdeki 3 yıl için elde edilmiştir.
Türkiye'nin Yanan Orman Alanının ARIMA Modeli ile Tahmini